Hubungan Dukungan Sosial Teman Sebaya terhadap College Adjustment pada Mahasiswa Rantau Tingkat Satu Diploma Tiga Keperawatan Abulyatama - Savinatun Najja; Urip Pratama; Ambia Nurdin (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
First-year out-of-town students face a challenging transition period because they have to adapt to new social and academic environments, college adjustment is the key to academic success and psychological well-being, and peer social support plays a crucial role in helping the adaptation process. The purpose of this study was to determine the correlation of peer social support with college adjustment for first-year out-of-town students in the Diploma Three Nursing Study Program at Abulyatama University. This study applied a quantitative method through a cross-sectional study approach and involved 109 populations. The sample consisted of 52 respondents selected through purposive random sampling using the Slovin formula. The instruments implemented include the questionnaire MSPSS to measure peer social support, it was found that the Croncbach Alpha for the family subscale was 0.81, the friend subscale was 0.82, and other significant subscales was 0.75 and SACQ to measure the level of college adjustment, it was found that the Alpha coefficient = 0.877, while the analysis used was univariate and bivariate by applying the chi square test. The study findings are based on the test findings using Chi-Square, it is known that the ρ value = 0.036 (≤ 0.05). The conclusion contains a correlation between peer social support and college adjustment in first-year out-of-town students. The results of this study are expected to be input for out-of-town students to improve their ability to adjust to the campus environment by utilizing peer social support. Educational institutions are expected to provide guidance or counseling programs that support the adaptation process of new students, especially out-of-town students. In addition, further research is expected to examine other factors that influence student adjustment, such as family and environmental factors, and use more diverse research methods to enrich the research results.